Effect of morphology and non-metal doping (P and S) on the activity of graphitic carbon nitride toward photoelectrochemical water oxidation - Aboubakr, Ahmed Esmail A.; El Rouby, Waleed M.A.; Khan, Malik Dilshad; Revaprasadu, Neerish; Millet, Pierre (Solar energy materials and solar cells, 2021)
The production of molecular hydrogen by photoelectrochemical dissociation (PEC) of water is a promising technique, which allows the direct transformation of solar energy into hydrogen, an energy vector acclaimed by the scientific community and policymakers. Hydrogen stores solar energy and will help overcome the energy crisis and associated environmental problems. Currently, the design and development of innovative photocatalysts with strong photoelectrochemical activity remain a major challenge, and the subject of intense research activity within the international scientific community. Here we describe the synthesis and photoelectrochemical properties of one-dimensional nanostructures of graphitic carbon nitride (1D-gC3N4) doped with phosphorus or sulfur (1D-P-gC3N4 &1D-S-gC3N4, respectively). A new synthesis method using supramolecular melamine, ammonium dihydrogen phosphate, and tri-thiocyanuric acid as precursors has been developed. The samples were characterized by powder-X Ray diffraction (p-XRD), X-Ray spectroscopy (EDS), transmission electron microscopy (TEM), Ultraviolet–visible (UV–Vis) spectroscopy, Fourier transform infrared spectra (FT-IR) and photoluminescence (PL) analysis. The activity towards the photo-oxidation of water was studied by linear scanning voltammetry (LSV). Compared to 3D material, the activity was found to be significantly improved, thanks in particular to the 1D morphology of gC3N4. It was further strengthened by doping with phosphorus and sulfur. The photo-oxidation mechanism of water was analyzed by photoelectrochemical impedance spectroscopy (PEIS). The measurements show that the resistance to charge transfer at the electrode/electrolyte interface can be greatly reduced by controlling the morphology of gC3N4, and that doping with phosphorus and sulfur also plays a positive role. The PEIS analysis makes it possible to demonstrate that the lifetime of the photo-generated electrons in 1D-gC3N4 is increased compared to 3D-gC3N4, and that doping with phosphorus or sulfur further improves it. The width of the forbidden bands and the position of the valence and conduction bands of the different materials were determined by Mott - Schottky type measurements. [Display omitted] •1D-gC3N4 doped with phosphorus and sulfur (1D-P-gC3N4 &1D-S-gC3N4) were prepared.•Electron-hole separation was enhanced after doping as compared to pristine 1D-gC3N4.•PEIS analysis exhibited improved charge transfer across solid/electrolyte interface after doping.•Mott – Schottky measurements were carried out to determine the band structures.•Hybrids showed higher photo-oxidation properties relevant to pristine 1D-gC3N4.